THE IMPACT OF ARTIFICIAL INTELLIGENCE ON QUALITY GOVERNANCE IN THE HEALTH SECTOR: A REVIEW OF GLOBAL MODELS AND STANDARDS - Ilhem, Yahiaoui; Ahmed Amine, Tiffrent (The journal of contemporary issues in business and government, 2025)
This study seeks to investigate the strategic potential of Artificial Intelligence in enhancing quality governance within the healthcare sector, with a specific focus on internationally recognized standards such as ISO 9001, ISO 13485, JCI, and EFQM. Employing a theoretical and analytical methodology, the paper draws upon global best practices and critically assesses their relevance and applicability to the Algerian healthcare system. The analysis highlights Artificial Intelligence’s capacity to strengthen patient safety, support data-driven decision-making, and enhance compliance with quality standards. However, the study also identifies significant structural and institutional barriers that may impede the adoption of Artificial Intelligence technologies in developing contexts. The findings underscore the need for a comprehensive national strategy that includes the development of a robust regulatory framework, targeted investments in digital infrastructure, and the promotion of evidence-based governance to facilitate effective Artificial Intelligence integration in Algerian healthcare.